Implementation of the Duties of the Village Consultative Body in the Interim Village Head Election in Bondowoso - Abidin, Ali Zaenal; Fauziyah, Fauziyah (MIMBAR YUSTITIA : Jurnal Hukum dan Hak Asasi Manusia, 2026)
This study examines the implementation of Article 37 letter h of the Bondowoso Regency Regional Regulation Number 2 of 2020 concerning the duties of the Village Consultative Body (BPD) in holding special village deliberations for the Election of the Interim Village Head (PAW). The background of this research departs from the gap between the normative framework that requires inclusive, democratic, and representative participation and the empirical reality that often shows the dominance of local elites and the lack of community involvement at large. The purpose of this study is to analyze the extent to which BPD's duties in PAW are carried out effectively in accordance with regulatory provisions, as well as to identify obstacles faced in their implementation. This study uses a normative juridical method combined with historical and conceptual approaches. The normative approach is carried out through the study of relevant laws and regulations, a historical approach tracing the development of PAW governance, and a conceptual approach examining academic views and participatory democratic theory. The findings of a case study in Pelalangan Village, Cermee District, show that although procedurally the implementation of PAW has been in accordance with applicable regulations, it still substantially does not meet the principle of fair representation. Village deliberative forums are dominated by certain community leaders, while women's groups, youth, marginalized communities, and the general public are less involved. The causative factors include low public legal literacy, the absence of clear technical guidelines regarding the composition of representation, and the lack of public information disclosure. This study concludes that the implementation of PAW requires regulatory reform, the preparation of technical guidelines for inclusive participation, and sustainable community empowerment to ensure democratic legitimacy. Strengthening structural and cultural aspects is the key to realizing a fair, participatory, and reflective PAW that reflects the aspirations of the entire community.